Spatial Distribution of HivAids Cases and Accessibility to Treatment Centers in Sunyani Municipality - Agbedra, S.Y. (University Of Ghana, 2018)
Introduction Satisfactory allocation of resources is essential as far as efforts to combat HIV/AIDS menace, especially in Africa. In determining HIV patients location, the nature of services must be in line with the behavioral, geographic and the social characteristics of the patients. This study, therefore, examined the spatial distribution of HIV cases and accessibility to treatment centers in the Sunyani Municipality. Methods To enable spatial analysis of HIV patterns, the locations of clients were geocoded. The 978 cases came from 44 unique communities in the Sunyani municipality. Summary descriptive statistics of demographic characteristics and other important HIV indicators were done. Spatial analysis was done to show the distribution of HIV cases in the Municipality. Also, Morans' I statistics were computed to find out if there was clustering. Paired t-test was done to determine the mean distance traveled to the ART centers. Placemarks were used to extract locations, it was exported as xml and converted into geodatabase feature classes using ArcGIS conversion tools. Results From the study, most communities such as Fiapre, Odumase, and Abesim with a high prevalence of cases were located at the periphery of the municipality. Also, communities along New Dormaa to Chiraa stretch recorded a high number of cases compared with other other communities linking the municipality. However, access to the ART centers in the periphery communities was low with the minimum distance traveled been 5.96km. Conclusion The results suggested that analysis of facility-based data could provide a more robust estimation of a broad spatial distribution of the HIV case in the Municipality. However, similar analyses should be conducted in other Municipalities with equally high prevalence rates to assess whether these patterns are observed elsewhere.
MSc.
Keywords: Hiv Aids; Treatment Centers; Sunyani Municipality